Goblet cell-produced retinoic acid suppresses CD86 expression and IL-12 production in bone marrow-derived cells. (12th July 2018) - Xiao, Yangyan; de Paiva, Cintia S; Yu, Zhiyuan; de Souza, Rodrigo G; Li, De-Quan; Pflugfelder, Stephen C
Abstract: Conjunctival goblet cell loss in ocular surface diseases is accompanied by increased number of interleukin-12 (IL-12)-producing antigen-presenting cells (APCs) and increased interferon-γ (IFN-γ) expression. This study tested the hypothesis that mouse conjunctival goblet cells produce biologically active retinoic acid (RA) that suppresses CD86 expression and IL-12 production by myeloid cells. We found that conditioned media from cultured conjunctival goblet cells (CjCM) suppressed stimulated CD86 expression, NF-κB p65 activation and IL-12 and IFN-γ production in unstimulated and lipopolysaccharide-stimulated cultured bone marrow-derived cells (BMDCs) containing a mixed population of APCs. Goblet cell-conditioned, ovalbumin-loaded APCs suppressed IFN-γ production and increased IL-13 production in co-cultured OTII cells. The goblet cell suppressive activity is due in part to their ability to synthesize RA from retinol. Conjunctival goblet cells had greater expression of aldehyde dehydrogenases Aldh1a1 and a3 and ALDEFLUOR activity than cornea epithelium lacking goblet cells. The conditioning activity was lost in goblet cells treated with an ALDH inhibitor, and a retinoid receptor alpha antagonist blocked the suppressive effects of CjCM on IL-12 production. Similar to RA, CjCM increased expression of suppressor of cytokine signaling 3 (SOCS3) in BMDCs. SOCS3 silencing reversed the IL-12-suppressive effects of CjCM. Our findings indicate that conjunctival goblet cells are capable of synthesizing RA from retinol secreted by the lacrimal gland into tears that can condition APCs. Evidence suggests goblet cell RA may function in maintaining conjunctival immune tolerance and loss of conjunctival goblet cells may contribute to increased Th 1 priming in dry eye. Abstract : Conjunctival goblet cells suppress APCs via retinoic acid